Relationship of Surface Pollen with Climate and Vertical Vegetation Communities in Subtropical Mountainous in Southern China - Quan Xiaowen; Huang Kangyou; Shui Kunchun; Li Hongwei; Xie Dehao; Zuo Jintang; Cen Caifeng; Zheng Zhuo (Redai dili, 2022)
Pollen analysis is one of the environmental proxies useful for quantitative reconstruction of paleoecology and paleoclimate, and the establishment of a quantitative relationship between surface pollen and vegetation is crucial for accurate interpretation of paleoecology and paleoclimate from fossil pollen. In this study, to explore the relationships between surface pollen assemblages and vegetation and altitude, 113 samples of modern surface pollen and moss were collected from the vertical vegetation zones in central south subtropical China. Based on the results of Canonical Correspondence Analysis (CCA), the study revealed the connections between the distribution of pollen taxa at different elevations and with various climate factors. The main results are as follows: 1) Castanopsis, Quercus-evergreen, Pinus, Cunninghamia and Euphorbiaceae were the dominant pollen taxa of the arbors, and Poaceae, Artemisia, Compositae, and Cyperaceae were the main components of the herbs. Trilete, Dicranopteris, Polypodiaceae and Monolete accounted for a high percentage of the fern pollen. 2) The relationships between pollen taxa and altitude could be divided into three patterns: Castanopsis, Quercus-evergreen, Pinus, Mallotus, Liquidambar, Rubiaceae,and Poaceae were common at the low altitudes (0-702 m). In the medium altitude area (703-1,299 m), there were significant pollen contents in Castanopsis, Cunninghamia, Pinus, Quercus-evergreen, Ericaceae and Pinus. The higher altitude area, at around 1,300-1,600 m, was dominanted by Castanopsis, Quercus-evergreen, and Fagus. Therefore, the distribution of surface pollen is consistent with that of modern vegetation. 3) The results of CCA showed that the climate factors controlling the distribution of surface pollen were Mean Annual Precipitation (MAP), Mean precipitation of warmest season (Mpwa), and Mean temperature of warmest season (Mtwa). It was obvious that the climate characteristics corresponded to high percentage values of various pollen, such as Pinus, Cunninghamia, Castanopsis, Quercus-evergreen, Theaceae, Fagus, and Quercus-deciduous. 4) The significant taxa of Castanopsis, Quercus-evergreen at lower elevations and Pinus, Cunninghamia and Fagus where grow at relatively high area can reflect the effects of climate factors on the spatial distribution of vegetation. Therefore, the results of this study indicated that the surface pollen assemblage varies significantly through the vertical vegetation zones in central south subtropical China. The characteristics of surface pollen dispersal were greatly influenced by the vegetation composition in the region, the habitat, pollen morphology, and the pollen transmission process, which provides a crucial reference for quantitative reconstruction of paleoecology and paleoclimate from fossil pollen data in a subtropical region.